2011
DOI: 10.1002/bit.23201
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo steady‐state model for galacto‐oligosaccharides synthesis with β‐galactosidase from Aspergillus oryzae

Abstract: A pseudo steady-state model for the kinetically controlled synthesis of galacto-oligosaccharides (GOS) with Aspergillus oryzae β-galactosidase is presented. The model accounts for the dynamics of lactose consumption and production of galactose, glucose, di, tri, tetra, and penta-oligosaccharides during the synthesis, being able to describe the total GOS content in the reaction medium at the experimental conditions evaluated. Experimental results show that the formation of GOS containing only galactose residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Recent researches in GOS synthesis with ␤-gal have shown that temperature increase generates a significant increase in GOS conversion [5,6], thereby it is necessary to obtain new active heterogeneous biocatalysts exhibiting high thermal stability and able to be reused. These objectives can be achieved by enzyme immobilization on solid supports, which also allows the development of continuous and sequential batch processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches in GOS synthesis with ␤-gal have shown that temperature increase generates a significant increase in GOS conversion [5,6], thereby it is necessary to obtain new active heterogeneous biocatalysts exhibiting high thermal stability and able to be reused. These objectives can be achieved by enzyme immobilization on solid supports, which also allows the development of continuous and sequential batch processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Variants of this model have been proposed aiming to a better description of the reaction system (Kim et al 2004;Neri et al 2009a) but they contain too many kinetic parameters that are difficult to estimate. We have constructed a simplified model that accounts for the synthesis of GOS-2, GOS-3, GOS-4 and GOS-5 containing a reduced number of kinetic parameters that can be determined by non-linear multiresponse fitting to experimental data (Vera et al 2011a). …”
Section: Enzymatic Synthesis Of Galacto-oligosacaccharides (Gos)mentioning
confidence: 99%
“…GOS are oligosaccharides composed by a variable number of galactose units (from one to ten, usually from two to four) and a terminal glucose unit, linked mostly by β1-4 and β1-6 bonds (Casci and Rastall, 2006), even though some polygalactose oligosaccharides not containing glucose can also be formed at low levels during synthesis (Sanz et al 2002;Vera et al 2011a). Disaccharides (mostly galactoseglucose) are refereed as GOS-2, trisaccharides (mostly galactose-galactose-glucose) as GOS-3, tetrasaccharides (mostly galactose-galactose-galactose-glucose) as GOS-4 and so on.…”
Section: Enzymatic Synthesis Of Galacto-oligosacaccharides (Gos)mentioning
confidence: 99%
“…Several models have been proposed to describe oligosaccharide synthesis and simultaneous lactose hydrolysis, ultimately pointing for the need of a high initial lactose concentration, viz. 40% w / v and above [6,119122]. The recent findings of Vera and co-workers established that an increase in the initial lactose concentration only influences positively the maximum product yield, provided the lactose remains dissolved [6].…”
Section: Immobilized Carbohydrases In the Production Of Prebioticsmentioning
confidence: 99%